Rates of Infection After Pediatric ACL Reconstruction: A Marketscan Database Study of 44, 501 Patients. Issue 5 (31st May 2022) - Block, Andrew M.; Eisenberg, Matthew; Vopat, Matt; Nepple, Jeffrey J.
Introduction: Anterior cruciate ligament reconstruction (ACL-R) is increasingly performed in pediatric patients. Infection after ACL-R is among the most serious complications. The use of administrative data has been validated for the assessment of infection after ACL reconstruction. While infection after ACL-R has been well investigated in adults, the literature is limited for ACL reconstruction in pediatric patients. Purpose: Describe and analyze the rates of infection after ACL-R among pediatric patients, compared to young adult patients, utilizing the MarketScan database. Methods: The Truven Health Analytics MarketScan Commercial Claims and Encounters database was assessed to access health care utilization data for privately insured individuals aged 5-30 years old. ACL-R records performed between 2006 and 2018 were obtained using Current Procedures Terminology (CPT) and International Classification of Diseases Ninth Revision (ICD-9) and Tenth (ICD-10) codes. The presence of postoperative infection requiring reoperation was assessed utilizing previously published algorithms. All patients had at least 180 days of insurance coverage after intervention. Results: The ACL-R cohort included 44, 501 individuals under 18 years old and 53, 915 individuals aged 18-30 years old. The rate of infection after ACL-R in patients under 18 years of age was 0.52%, and was similar to patients 18-30 years old (0.47%, p=0.213). Among patients <18 years old, patients <15 years old had a significantly lower rate of infection at 0.37% compared to adolescents (15.0-17.9 years old) at 0.55% (p=0.039). For those less than 18 years old, males were significantly more likely to have an infection after ACL-R (0.73%) compared to females (0.53%, p=0.008). Discussion: Utilizing an insurance database, this study demonstrated that rates of infection after an ACL-R are relatively low (0.52%) and are similar to rates in young adults, despite the differences in graft utilization. Both age less than 15 and female sex were associated slightly lower rates of infections in pediatric patients. Figure 1. Rates of infection after ACL-Reconstruction (ACLR) in each age group over the study time period. There was significant difference in rate of infection in those <18 years old, Adolescents (15.0-17.9 years old) had significantly higher rate of infection than Pediatric patient (<15.0 years old). No differences were observed for those older than 18 years old (Young Adult [18.0-24.9 years old] and those >18 years old.